2017
DOI: 10.18632/oncotarget.23096
|View full text |Cite
|
Sign up to set email alerts
|

Glycan microarray reveal induced IgGs repertoire shift against a dietary carbohydrate in response to rabbit anti-human thymocyte therapy

Abstract: Humans have circulating antibodies against diverse glycans containing N-glycolylneuraminic acid (Neu5Gc) due to function-loss mutation of the CMAH gene. This xenogenic non-human carbohydrate is abundant in red meat, xenografts and biotherapeutics. Low levels of diet-derived Neu5Gc is also present on normal human endothelial cells, and together with anti-Neu5Gc antibodies could potentially mediate “xenosialitis” chronic-inflammation. Rabbit anti-human thymocyte globulin (ATG) is a drug containing polyclonal IgG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 33 publications
2
51
0
Order By: Relevance
“…The detailed analysis of the arrays performed on eight patients in this study showed a clear increase in the anti‐Neu5Gc IgG repertoire and reactivity at 6 months post‐ATG, in contrast to the controls. Despite the major immunosuppression, these data fit with those obtained in non‐immunosuppressed patients . These results thus sustain the possibility that ATG can extend the pre‐existing anti‐Neu5Gc antibodies’ repertoire to new specificities, leaving xenosialitis conceivable.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The detailed analysis of the arrays performed on eight patients in this study showed a clear increase in the anti‐Neu5Gc IgG repertoire and reactivity at 6 months post‐ATG, in contrast to the controls. Despite the major immunosuppression, these data fit with those obtained in non‐immunosuppressed patients . These results thus sustain the possibility that ATG can extend the pre‐existing anti‐Neu5Gc antibodies’ repertoire to new specificities, leaving xenosialitis conceivable.…”
Section: Discussionsupporting
confidence: 80%
“…Animal‐derived molecules or engineered tissues are highly immunogenic. ATG, a widely used polyclonal rabbit IgG preparation that expresses α‐Gal and Neu5Gc‐glycans according to a mass spectrometry analysis, induces a vigorous response against these two xeno‐antigens in non‐immunosuppressed patients . However, as for allo‐antibodies, the immune response against these foreign glycans was dramatically delayed and decreased by modern immunosuppressive cocktails, as recently described .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…High titers of elicited anti‐Neu5Gc Abs are also generated following exposure to animal‐derived products or proteins, such as after polyclonal rabbit anti‐human T‐cell globulin (ATG) infusion . Such elicited anti‐Neu5Gc Abs also display higher affinity and an extended repertoire of responses against new Neu5Gc epitopes than diet‐derived anti‐Neu5Gc Abs, and some are not present before immunization, as demonstrated by sialoglycan microarrays . Thus, in addition to the expected deleterious interaction with the immunizing animal‐derived material, such elicited anti‐Neu5Gc Abs can also result in the formation of in situ immune complexes and chronic inflammation in the micro‐vicinity of the recipients' own Neu5Gc‐positive endothelial cells (ECs) .…”
Section: Introductionmentioning
confidence: 99%